1786 N.H. Laws 383-84 - (:unkn) unknown (My University, 1786)
An Act to Prevent the Keeping of Large Quantities of Gun-Powder in Private Houses in Portsmouth, and for Appointing a Keeper of the Magazine Belonging to Said Town: That if any person or persons, shall keep in any dwelling-house, store or other buildings, on land, within the limits of said Portsmouth, except the magazine aforesaid, more than ten pounds of gun-powder at any one time, which ten pounds shall be kept in a tin canister properly secured for that purpose, such person or persons shall forfeit the powder so kept,
Keywords: GUNPOWDER - STORAGE